A configuração do êxodo rural no assentamento Santa Rosa II Abelardo Luz SC: uma análise em construção 1986/2008 - Curioni, Antonio Sergio (2009)
The present dissertation takes as an object the configuration of the rural exodus in the Assentamento Santa Rosa II Abelardo Luz, SC: an analysis in construction 1986/2008. The objective aims to understand and to analyse for why families that were established by the Movement of the Rural Workers Without Land (MST) in the Assentamento Santa Rosa II, in the local city of Abelardo, SC, after they suffer the whole process of occupation, eviction and definite registration, after his property is installed and organized they sold his share and migrated for city. The lifted hypothesis can be considered multifatorial, of objective and subjective nature, with distinction for the difficulties of survival in the agriculture, weakening in the acting of the MST near the fixed families and lack of leisure options, culture, sport and health in the Assentamento. The adopted concepts of reference were: agrarian question, migration, rural exodus, MST and Land reform, based on classic and contemporary authors of the areas of the rural sociology, economy, history, geography and political sciences. The inquiry is of qualitative nature, having like proceedings methodologic, the bibliographical lifting, the documentary inquiry and he was seeing Internet, the observation participant of the investigator, and the field work. Principal instrument of collection of data in the empirical inquiry was used, the interview semi-structured with topical advisors. There were interviewed six subjects chosen between 27 families that went out from the Assentamento priorizing the six people that migrated for the city of Abelardo it shines, what they were possible of being located. The got informations were analysed through analysis of content. The results of the inquiry pointed that the MST for the immigrants is characterized like a movement of release, of struggle for rights the land, Land reform, social justice, popular sovereignity, as well as, favorable formation partner-politics of his participants, which provides means of individual and collective growth, becoming a school of life, as well as provides conquests that go very much besides the land and the own house, like knowledge, freedom, dignity and spirit of citizenship. The results point still that, in spite of the mentioned conquests the interviewed ones left the Assentamento and migrated for the city, being the principal motives: very small land and with bad lands, lack of agricultural credit, providing a low production, besides the distance and the difficult access to resources like health, education, social work, culture, sport and leisure